Financial Security in China Situation Analysis and System Design - He, Dexu (Research Series on the Chinese Dream and China's Development Path,, 2016)
This book studies typical issues regarding China's financial security, such as internal and external currency security, herd behavior in bank credit, system risk in the stock market, major risks in the insurance industry, risks related to shadow banking, and real-estate finance security. The book reflects the author's longtime research experience and personal thought. It uses a completely new structure to present useful and targeted-based countermeasures and suggestions, making it a valuable reference resource for those involved in solving China's financial security problems and creating China's future financial security system. It is highly recommended for readers who want to understand the current situation and features of China's financial security.